Synthesis and characterization of CoCrxFe2-xO4 nanoparticles - Hankare, P. P.; Sankpal, U. B.; Patil, R. P.; Mulla, Imtiaz S.; Lokhande, P. D.; Gajbhiye, N. S. (Journal of Alloys and Compounds, 2009)
Spinel-phase nanocrystalline CoCrxFe2-xO4 powders (0.0 <= x <= 2.0) were synthesized by citrate-gel precursor method. The samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM). transmission electron microscopy (TEM) and infra-red spectroscopy (FT-IR). The XRD and selected-area electron diffraction (SAED) patterns indicated that the synthesized nanoparticles have single-phase spinet structure without the presence of any other impurities. The changes in electrical and magnetic properties of different stiochiometric compositions have also been investigated. It is seen that with increase in chromium contents, the measured magnetic hysteresis loops become narrow with decreasing trend in saturation magnetization. Electrical resistivity indicated that all the compounds are semiconducting nature. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Magnetic measurements; Sintering; transmission electron microscopy; X-ray diffraction

Synthesis and characterization of nanocrystalline zinc substituted nickel ferrites - Hankare, P. P.; Sankpal, U. B.; Patil, R. P.; Mulla, Imtiaz S.; Sasikala, R.; Tripathi, A. K.; Garadkar, K. M. (Journal of Alloys and Compounds, 2010)
Nanocrystalline zinc substituted nickel ferrites, Ni(1-x)Zn(x)Fe(2)O(4) (0.0 <= x <= 1.0) have been prepared by citrate gel auto-combustion method. The effect of zinc ion content on structural, electrical transport and magnetic properties has been studied. The X-ray diffraction (XRD) pattern revealed that, all the compositions possess single-phase spinel structure. The nano-sized grain structure formation was confirmed by transmission electron microscopy (TEM). The dc electrical resistivity shows the samples are semiconducting in nature. The magnetic measurements showed that the composition Ni(0.6)Zn(0.4)Fe(2)O(4) has maximum saturation magnetization (M(s)) while high coersivity (Hc) for ZnFe(2)O(4). Thermoelectric power measurement study showed that the compounds, with x <= 0.4 are p-type and for x > 0.4 behaves n-type conduction mechanism. (C) 2010 Published by Elsevier B.V.
Keywords: Electron microscopy; Magnetic; Sintering; X-ray diffraction

Synthesis and characterization of cobalt substituted zinc ferri-chromites prepared by sol-gel auto-combustion method - Hankare, P. P.; Vader, V. T.; Sankpal, U. B.; Patil, R. P.; Jadhav, A. V.; Mulla, Imtiaz S. (Journal of Materials Science-Materials in Electronics, 2011)
Mixed metal oxides having spinel structure shows interesting structural properties. In the present investigation, cobalt substituted zinc ferri-chromites were prepared by sol-gel auto-combustion method. The completion of solid state reaction and the formation of spinel phase were identified using X-ray diffraction technique. All the compounds exhibit cubic spinel symmetry and lattice constant shows an irregular trend with substitution of Co. Infra-red spectral studies shows an two strong bands, one around 600 cm(-1) which is attributed to the intrinsic vibrations of tetrahedral complexes and the other at 400 cm(-1) is due to octahedral one. The morphology and size of the particles was found out by scanning electron microscopy while the elemental compositions by elemental dispersive X-ray spectroscopy. The various compounds of the present system Zn1-xCoxFeCrO4 were also investigated for their thermal and electronic studies.